The Effect Of Block Training On Block Skills In Extracurricular Volleyball Players At Man 02 Kepahiang - Defika, Yoba; Martiani, Martiani; Syaputra , Roni (Journal of Education, 2025)
This study aims to determine the effect of block training on block skills in extracurricular volleyball players at MAN 02 Kepahiang. This type of research is an experimental study with a sample of 16 students. The results of the study indicate that based on the results of data analysis, description, testing of research results, and discussion, it can be concluded: block training can significantly improve block skills". P = 0.000 <0.05, so it can be said that there is a significant change in block skills before being given treatment and block training after being given treatment. After Data Analysis was carried out using the statistical approach of the arithmetic mean difference test (t-test) at a significant level of α = 0.05 against the two research hypotheses proposed, both hypotheses were accepted and their truth could be tested. The hypothesis proposed in this study was proven to have an effect.